Playing with digital gender identity and cultural value. Issue 4 (2nd April 2016) - Chen, Chih-Ping
Abstract : In cyberspace, anything is possible. Playing with digital gender identity has particularly flourished in digital dating games. Women can become the 'masters, ' while men are the 'pets' when fabricating and manipulating digital gender identity to develop alternative heterosexual relationships. This implies that the breaking down of social and cultural barriers in cyberspace is possible if the digital dating game is seen as playful or a potential liberation from the barriers of digital gender identity to challenge the existing masculine power base. The current study attempts to fill the gap in knowledge related to challenging heterosexuality as the masculine dominant norm in cyberspace by examining Taiwanese online heterosexual relationship developments between gender identity and cultural value while playing a ludic digital dating game. The study employs netnography and recruits 40 people total, including Taiwanese workers and full-time university students, for participation in this research. The results highlight that the digital dating game is in some ways liberating, enabling Taiwanese users to present themselves as they want to express emotions, establish online heterosexual relationships in a nontraditional way, and engage in alternative digital gender play. These 'ludic gaps' allow for a fleeting, but unsustainable escape from traditional Taiwanese gender cultural values and practices. It is suggested that culture is inescapable, regardless of whether we are in the real world or cyberspace.